Evaluation of biomass yield and seed yield of vetch and oats variety mixtures - Yadeta, Gemechis Lencho (Journal of Scientific Agriculture, 2024)
A different species and varieties of forage vetch and oat were identified to successfully adapt and perform in the highlands of Bale. However, their oat-vetch mixture was not evaluated. The study was conducted to evaluate the effect of variety on biomass yield and seed yield of oats and vetch grown in pure stand and mixtures. This experiment was conducted at Sinana Agricultural Research Center, Bale zone, southern Ethiopia, during May 2023. A total of five treatments were developed for sole and mixed stands using two oat varieties and one vetch variety. A trial was arranged in RCBD with five replications. The recorded data are morphological parameters, biomass, tiller, side branch, seedling count and seed yield were calculated and subjected to analysis of variance (ANOVA) following the GLM procedures in SAS version 9.4. The highest dry matter yield (DMY) 18.6 t ha-1 was observed by the mixture of Gebisa variety + oat Bonsa variety. Among the mixture treatments, Gebisa variety + oat Bonsa variety had the highest seed yield (2.9 t ha-1) while the pure stand Bona-bas variety had the seed yield (1.28 t ha-1). The dry matter yield (DMY), of mixtures of Gebisa variety + oat Bonsa variety mixtures was better than pure stands. Based on the current result it is concluded that oat Bonsa variety + Gebisa variety mixtures had relatively higher yield biomass. Generally, in the present study on Oat-vetch mixture, there is higher yield biomass so, Animal performance must be tested.